Male, Pale, and Stale? Diversity in Lawyers' Regulatory Leadership - Semple, Noel (2016)
When lawyers elect the leaders of their self-regulatory organizations, what sort of people do they vote for? How do the selection processes for elite lawyer sub-groups affect the diversity and efficacy of those groups? This article quantitatively assesses the demographic and professional diversity of leadership in the Law Society of Upper Canada.
Keywords: Noel Semple